War and literature - Ashe, Laura; Patterson, Ian (Suffolk : Boydell & Brewer, 2014)
War was the first subject of literature; at times, war has been its only subject. In this volume, the contributors reflect on the uneasy yet symbiotic relations of war and writing, from medieval to modern literature. War writing emerges in multiple forms, celebratory and critical, awed and disgusted; the rhetoric of inexpressibility fights its own battle with the urgent necessity of representation, record and recognition. This is shown to be true even to the present day: whether mimetic or metaphorical, literature that concerns itself overtly or covertly with the real pressures of war continues to speak to issues of pressing significance. Particular topics addressed include writings of and about the Crusades and battles during the Hundred Years War; Shakespeare's'Casus Belly'; Auden's'Journal of an Airman'; and War and Peace. Contributors: Joanna Bellis, Catherine A.M. Clarke, Mary A. Favret, Rachel Galvin, James Purdon, Mark Rawlinson, Susanna A. Throop, Katie J. Walter, Carol Watts, Tom F. Wright, Andrew Zurcher.
Acts of vengeance, acts of love : crusading violence in the twelfth century / Susann A. Throop -- Peril, flight and the Sad Man : medieval theories of the body in battle / Katie L. Walter -- 'Is this war?' : British fictions of emergency in the Hot Cold War / James Purdon -- Crossing the Rubicon : history, authority and civil war in twelfth-century England / Catherine A.M. Clarke -- 'The reader myghte lamente' : the sieges of Calais (1346) and Rouen (1418) in chronicle, poem and play / Joanna Bellis -- Shakespeare's casus belly, or, Cormorant war, and the wasting of men on Shakespeare's stage / Andrew Zurcher -- Unnavigable kinship in a time of conflict : Loyalist calligraphies, sovereign power and the'muckle honor' of Elizabeth Murray Inman / Carol Watts -- Proclaiming the war news : Richard Caton Woodville and Herman Melville / Tom F. Wright -- A feeling for numbers : representing the scale of the war dead / Mary A. Favret -- The guilt of the noncombatant and W.H. Auden's'Journal of an airman' / Rachel Galvin -- Does Tolstoy's War and peace make modern war literature redundant? / Mark Rawlinson.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: War in literature; War and literature